2012
DOI: 10.1002/bjs.8909
|View full text |Cite
|
Sign up to set email alerts
|

KRAS status and outcome of liver resection after neoadjuvant chemotherapy including bevacizumab

Abstract: This study provided further evidence for the prognostic importance of KRAS status in terms of recurrence-free and overall survival. Neoadjuvant chemotherapy including bevacizumab elicited a response, irrespective of KRAS status, in this selected group of patients with CLM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 31 publications
(49 reference statements)
4
63
1
2
Order By: Relevance
“…Indeed it's possible that both KRAS and BRAF mutations are associated with a worse biology and a more rapid and aggressive metastatic behavior of CLM, discouraging surgeons to perform surgical resection, independently of clinical resectability. This interpretation is consistent with the evidence that the percentage of KRAS mutated patients ranged from 14% (Stremitzer et al, 2012) to 37% (Teng et al, 2012) in all seven included studies, compared to 35-45% reported in metastatic and unresectable CRC, suggesting a significant association between KRAS mutations rates and tumor behavior, as described in preclinical studies (Suchy et al, 1992;Tanaka et al, 1994;Varghese et al, 2002;Webb et al, 1998). Some clinical series have also shown that KRAS mutations are associated with an increased risk of developing lung and liver metastases compared to wild-type population (Vauthey et al, 2013;Kemeny et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Indeed it's possible that both KRAS and BRAF mutations are associated with a worse biology and a more rapid and aggressive metastatic behavior of CLM, discouraging surgeons to perform surgical resection, independently of clinical resectability. This interpretation is consistent with the evidence that the percentage of KRAS mutated patients ranged from 14% (Stremitzer et al, 2012) to 37% (Teng et al, 2012) in all seven included studies, compared to 35-45% reported in metastatic and unresectable CRC, suggesting a significant association between KRAS mutations rates and tumor behavior, as described in preclinical studies (Suchy et al, 1992;Tanaka et al, 1994;Varghese et al, 2002;Webb et al, 1998). Some clinical series have also shown that KRAS mutations are associated with an increased risk of developing lung and liver metastases compared to wild-type population (Vauthey et al, 2013;Kemeny et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Three of these studies were retrospective series (Vauthey et al, 2013;Kemeny et al, 2014;Francesca Bergamo and Loupakis et al, 2014), while the others were prospective studies (Nash et al, 2010;Karagkounis et al, 2013;Stremitzer et al, 2012;Teng et al, 2012). In these 7 studies, sample sizes of the analyzed population ranged from 60 (Stremitzer et al, 2012) to 309 (Schirripa et al, 2015), while the percentage of KRAS mutated patients ranged from 14% (Stremitzer et al, 2012) to 37% (Teng et al, 2012). BRAF mutations were analysed in four of the seven included studies (Karagkounis et al, 2013;Stremitzer et al, 2012;Teng et al, 2012), and it was found in 2-4% of patients who underwent surgery for CLM.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations